The praxis of radical placemaking - Gonsalves, Kavita; Caldwell, Glenda Amayo; Foth, Marcus (Frontiers in Computer Science, 2023)
Emerging from social disparities of the COVID-19 pandemic and contestations of marginal bodies in space during the Black Lives Matter global movement, Radical Placemaking is proposed as a digital placemaking design practice and investigated as part of a three year design study. This practice involves marginalised bodies highlighting social issues through the ephemerality and spectacularity of digital technologies in public space in [smart] cities. Radical Placemaking methodology, as demonstrated through three design interventions, engages participatory action research, slow design and open pedagogies for marginal bodies to create place-based digital artefacts. Through the making and experience of the artefacts, Radical Placemaking advances and simulates a virtual manifestation of the marginal beings' bodies and knowledge in public spaces made possible through emerging technologies. Through 9 key strategies, the paper offers a conceptual framework that imbibes a relational way of co-designing within the triad of people-place-technology.